2023
DOI: 10.3389/fnhum.2023.1200393
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting: expanding the extra-pharmacological model of psychedelic drug action to incorporate delayed influences of sets and settings

Nicolas Garel,
Julien Thibault Lévesque,
Dasha A. Sandra
et al.

Abstract: BackgroundPsychedelic drug experiences are shaped by current-moment contextual factors, commonly categorized as internal (set) and external (setting). Potential influences of past environments, however, have received little attention.AimsTo investigate how previous environmental stimuli shaped the experiences of patients receiving ketamine for treatment-resistant depression (TRD), and develop the concept of “imprinting” to account for such time-lagged effects across diverse hallucinogenic drugs.MethodsRecordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…By reducing the external stimuli that ground patients in their physical environments, patients describe blindfolds as greatly increasing the degree and intensity of perceptual changes induced by ketamine. Likely as a result of blindfolds and other contextual factors, and in contrast to others ( 166 ), we have consistently found that subanesthetic dosages of ketamine, e.g., 0.5 mg/kg, can produce powerfully psychedelic experiences including high scores on the Mystical Experience Questionnaire ( 164 , 167 ).…”
Section: Methodssupporting
confidence: 48%
See 2 more Smart Citations
“…By reducing the external stimuli that ground patients in their physical environments, patients describe blindfolds as greatly increasing the degree and intensity of perceptual changes induced by ketamine. Likely as a result of blindfolds and other contextual factors, and in contrast to others ( 166 ), we have consistently found that subanesthetic dosages of ketamine, e.g., 0.5 mg/kg, can produce powerfully psychedelic experiences including high scores on the Mystical Experience Questionnaire ( 164 , 167 ).…”
Section: Methodssupporting
confidence: 48%
“…In this article, we present the Montreal model of ketamine for TRD, a biopsychosocial approach developed gradually over years of real-world clinical experiences and research endeavors. Our aim has been to help bridge the current divide between biomedical and psychedelic models of ketamine while aiding in the interpretation of our recent and upcoming research results ( 12 , 13 , 145 , 164 , 169 ). We have thus endeavored to provide sufficient information for researchers and clinicians from diverse backgrounds to understand our approach, from its theoretical underpinnings up to its session activities and clinical implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation